2015
DOI: 10.1111/ppc.12124
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Patients and Their Relatives Toward Electroconvulsive Therapy in China

Abstract: Mental health professionals need to address the inadequate information on ECT provided to patients and their relatives prior to the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
7
18
0
Order By: Relevance
“…Of the adverse effects, memory impairment is the most common concern to patients . About two‐thirds of older patients reported memory impairment in our study, which is similar to the figure (65.7%) reported in adult studies …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Of the adverse effects, memory impairment is the most common concern to patients . About two‐thirds of older patients reported memory impairment in our study, which is similar to the figure (65.7%) reported in adult studies …”
Section: Discussionsupporting
confidence: 89%
“…Similar to previous findings in adult patients, the majority of older patients and their caregivers appear to receive adequate information about the therapeutic effects of ECT. However, inadequate information was provided about the ECT process, adverse effects, and risks prior to ECT.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Thirst or dry mouth was reported in the AD group of all studies, while sleepiness was reported only in the ECT group in one study. As found previously, most side‐effects were transient . The discontinuation rate was reported in only one study, but group differences were not observed .…”
Section: Discussionsupporting
confidence: 79%